The Perception of Women with Postpartum Depression Towards Family Supports - Ida Maryati; Niken Fitri Astuti; Tetti Solehati (Journal of Maternity Care and Reproductive Health, 2018)
AbstractMental health is a global problem including postpartum blues.  Woman's perception of family’s support may increase postpartum blues symptoms. The purpose of this study was to describe the perceptions of women with postpartum blues towards family supports in Al Islam Hospital, Bandung, Indonesia. The design was descriptive and samples were chosen using the purposive sampling technique. The number of respondents was 35 women, and the data were gathered using two questioners. There were family support and modification of Kennerly and Gath's questioner. The results showed that most of respondent's perceived family provided emotional support 75%, instrument support 51%, reward support 54%, and informational support 54%. Based on the result, it is an opportunity for the hospital to provide counseling or health education to patient or family about the patient need on family support.Keywords: Family Support, Perception, Postpartum Blues